Signal Processing, Speech and Music - Tempelaars, Stan (Lisse Swets & Zeitlinger, 1996)
This text offers a comprehensive introduction to the theory of signals and systems and the way in which this theory is applied to the study of acoustic communication (both digital and analogue): the development of systems for producing, transmitting and processing speech and music signals. The book is designed to make the reader acquainted with the refined and powerful theoretical and practical tools available for this purpose. The book teaches understanding of such concepts as amplitude and phase spectrum, impulse and frequency response, amplitude and frequency modulation, as well as such methods for the analysis and synthesis of speech and musical systems like LPC and wave shaping. The use of complex numbers is avoided and a knowledge of mathematics beyond that of secondary school level is not necessary.Show More Show Less